2018
DOI: 10.24953/turkjped.2018.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Management of NSAID-related pyloric obstruction in a child using endoscopic balloon dilatation: A case report

Abstract: Öztan MO, Güngör-Takeş G, Çağan-Appak Y, Yıldız C, Karakoyun M, Baran M. Management of NSAID-related pyloric obstruction in a child using endoscopic balloon dilatation: A case report. Turk J Pediatr 2018; 60: 765-768.A gastric outlet obstruction (GOO) is a major complication of peptic ulcers (PUs) and corrosive ingestion in children; however, the optimal management of a patient with a GOO after a PU remains controversial. Although surgical correction is the most common treatment option, endoscopic balloon dila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…[ 28 ] Therefore, it has been recommended that endoscopic pyloric balloon dilatation be attempted before surgery in children with ulcerative scarred pyloric obstruction, [ 29 ] especially in children with peptic ulcers induced by NSAID medication use. [ 30 ] However, studies have also shown that the long-term success of endoscopic therapy for ulcerative incisional pyloric stenosis in adolescent patients is questionable. One case reported a failed attempt at endoscopic balloon dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] Therefore, it has been recommended that endoscopic pyloric balloon dilatation be attempted before surgery in children with ulcerative scarred pyloric obstruction, [ 29 ] especially in children with peptic ulcers induced by NSAID medication use. [ 30 ] However, studies have also shown that the long-term success of endoscopic therapy for ulcerative incisional pyloric stenosis in adolescent patients is questionable. One case reported a failed attempt at endoscopic balloon dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in this case, pyloric stenosis can be readily diagnosed and effectively managed by endoscopic approaches even in pediatric patients. 11,12 In all, we highlight an uncommon but serious adverse effect of gastric outlet obstruction, potentially associated with celecoxib as part of metronomic therapy delivered for relapsed medulloblastoma. Gastrointestinal toxicities should be systematically evaluated in these protocols.…”
Section: Gastric Outlet Obstruction In a Patient With Relapsed Medull...mentioning
confidence: 97%
“…Se han utilizado técnicas endoscópicas complementarias para aumentar la eficacia de la DEB en las estenosis benignas refractarias, incluidas, entre otras, la inyección de esteroides locales intralesionales como la triamcinolona 5,6 y la incisión endoscópica con electrocauterización. 7,8 Se presenta un paciente pediátrico con una estenosis prepilórica secundaria a enfermedad ulceropéptica, sin respuesta al tratamiento médico, que requirió dilataciones progresivas neumáticas y la combinación con otras técnicas endoscópicas, como la inyección de triamcinolona e incisiones con electrocauterio.…”
Section: Introductionunclassified